O retorno do investimento nas categorias de base de times brasileiros - Franchini, Leonardo Dall Agnol (2023)
This article discusses the impact of investment in the youth categories of Serie A football teams in Brazil, considering recent changes in the sporting and economic scenario. The research focuses on the relationship between investment in the youth categories and the economic return for Serie A clubs in Brazil. Information is collected on how much more certain Brazilian clubs invest in their youth categories and the value and return on these investments is assessed. Football is a popular sport in Brazil and highlights the evolution of the sport, with a significant increase in investments, making it inflated. Brazilian football revenue exceeded 100 billion reais, becoming greater than the GDP of many countries. Given the social inequality in Brazil, many Brazilians see professionalization in football as an opportunity to change their lives. The clubs studied were Grêmio, Palmeiras, Flamengo, Athletico Paranaense and São Paulo, which are the Brazilian football teams best evaluated by the conmebol ranking. Within this context, the research presents the following question: What is the relationship between investment in youth categories and economic return for Series A clubs in championships and player sales? The main objective is to analyze how investment in youth categories affects performance financial and club achievements. The specific objectives would be to define criteria for the selection of teams to be studied, identify the investments made in the youth categories in the analyzed period, identify the values in prizes for titles won and sales values of players formed by the base of the clubs studied and establish correlations between the variables, identifying and ranking the clubs with greater efficiency and return on investments made in the youth categories. The data was found through online searches and publications. Information was found and results were obtained that show how impactful good management of youth categories is, when it is well applied, as in the case of these teams, the returns obtained are of great importance, both financially and in terms of good placements in championships. In the results obtained, we have as a great example of management, Athletico Paranaense, which achieved an impressive return on its investments in this area, generating a return multiplier compared to revenue from championships and sales of base players of 15,67. And the worst, but not with a bad return, was São Paulo, which obtained a return multiplier of 4,11, which shows how effective an adequate investment in this area can be. Therefore, it is recommended that clubs continue to evaluate and monitor the status of their investments in this area, so that results can continue to improve. With this, the objectives were achieved, as with the research carried out it was possible to analyze and see how effective the clubs' investment is from their youth categories, and satisfactory results were obtained.